Aplicación de hábitos de higiene en la manipulación de alimentos, por las madres de familia de la escuela fiscomisional Cristóbal Colón San Pablo de Ushpayacu, Archidona. Año 2015 - Cerda Grefa, Rosa Isabel (2016)
The investigation was intended to determine the application of hygiene habits in food handling, for mothers of Fiscomisional Christopher Columbus School, San Pablo de Ushpayacu, Archidona. 2015. Observation techniques and survey instruments, the observation guide and questionnaire to 33 mothers was applied. The design was cross-sectional, descriptive, analytical, field and literature. As a result the 42. 42% of 20 to 29 years are the most numerous. The indigenous ethnic group predominates 97.97%, the educational level is high at 51.52%, the occupation agriculture 42.42%, the population socioeconomic level of the population is low with 75,76%. Reference in determining the application of hygiene in food handling; 75.76% is the application level, do not wash their hands 9.09%, do not practice daily bath at 69.70%, 100% clean clothes, have short nails 15,15%, do not have the hair in 90.91%, 90.91% do not use mandil not wear rings 100%, do not wash fruits 84,85%, test and returns to get her spoon in the same preparation 90.91%, do not cover preparations to avoid contamination 9.09%, do not perfom washes immediate utensils 100%, boil water for consumption 100%, keeping the kitchen clean 100 % , 15.15%, do not have clean utensils and covered 100%, do not monitor the hand washing in children the non. Data calculed using the do not application of hygiene: 39,39% is the unfamiliarity and lack of barriers and measures 93,53%. It is concluded that the implementation of good practices developed hygiene habits.